Systems of essentially infinite-dimensional differential equations - Statkevych, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We investigate systems of differential equations with essentially infinite-dimensional elliptic operators (of the Laplace - Levy type). For nonlinear systems, we prove theorems on the existence and uniqueness of solutions. For a linear system, we give an explicit formula for the solution.